LEGAL IMPLICATIONS OF PIG-CONTAMINATED IRRIGATION WATER IN ERETON KULON: A FOUR-SCHOOL JURISPRUDENTIAL ANALYSIS - Yusrizal, Navis; Hakim, Rifki Arfanul; Kamaluddin, Hilmi; Al Mujaradah, Sulasiah (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
The practice of bathing pigs in rice field irrigation channels in Ereton Kulon Village, Indramayu, raised concerns among the local Muslim community regarding the potential contamination of irrigation water and its impact on crops. This study examines the concept of impurity (najāsah) in classical Islamic jurisprudence and its application to such agricultural contexts. It addresses two primary questions: whether irrigation water contaminated by pigs becomes legally impure, and whether crops irrigated or fertilized with such water or substances are permissible for consumption. Using a qualitative literature review approach, data from classical fiqh texts and supporting secondary sources were analyzed through a descriptive-analytical method. The findings indicate consensus among scholars that water becomes impure when its essential properties—color, taste, or odor—are altered. Divergence arises in defining the threshold of a “large quantity” of water: the Shafi’i and Hanbali schools set it at two qullahs, whereas the Hanafi and Maliki schools apply alternative criteria. Regarding crop consumption, the majority of scholars, including the Maliki school and certain Shafi’i jurists, permit it, while the Shafi’i position maintains prohibition. The Hanbali school allows consumption under the condition of tangible benefit (intifa’). This study highlights the practical relevance of classical fiqh perspectives on impurity in contemporary agricultural contexts and informs the legal assessment of crops exposed to contaminated irrigation.